Case Report: Hemangioblastoma- Like Clear Cell Stromal Tumor of the Left Lower Lung - Zhang, Xiaowei; Huang, Bifei; Jiang, Hongquan; Wei, Hangping (Frontiers in Medicine, 2022)
Background Hemangioblastoma-like clear cell stromal tumor (HLCCST) is a recently reported neoplasm of the lung. Only 13 cases have been reported in four recent studies. Because HLCCST is very rare, it has not been included in the 2021 WHO classification of lung tumors. Case Presentation We report a case of HLCCST of the left lower lung in a 40-year-old female who was admitted to our hospital after pulmonary nodules were discovered. A plain chest CT scan showed a nodular high-density shadow measuring approximately 8 mm in diameter in the left lower lung. The lesion had clear borders, uneven internal density, and a low-density central vacuolar area. The left lower lung was partially resected by video-assisted thoracic surgery. Post-operative histopathologic diagnosis “hemangioblastoma-like clear cell stromal tumor” of the left lower lung. Conclusion The HLCCST is an extremely rare tumor and needs long-term follow-up after operation. Clinically, it may be easily confused with other benign and malignant tumors of the lung, and diagnosis is solely determined by histopathologic examination. This case suggests that immunohistochemical CD34 can be a strong positive marker.